Commensal-to-pathogen transition: One-single transposon insertion results in two pathoadaptive traits in Escherichia coli -macrophage interaction - Proença, João T. (2017)
There are no funders and sponsors indicated explicitly in the document. This deposit is composed by the main article plus the supplementary materials of the publication.